The Property Rights Approach to Nonprofit Organization: The Role of Intrinsic Motivation - Valentinov, Vladislav (Public organization review, 2007)
The standard property rights approach to nonprofit organization claims that attenuation of property rights in the form of nondistribution constraint stimulates managerial shirking in nonprofit firms and thereby makes them less efficient than for-profit firms. This paper argues that this view neglects the important role played by intrinsic motivation in nonprofit organization. Intrinsically motivated stakeholders provide resources to nonprofit firms and thereby facilitate their economic survival. However, intrinsic motivation is subject to the crowding-out effect, i.e., the danger of being displaced by the use of extrinsic (monetary and administrative) incentives. The property rights structure in nonprofit organization is designed to minimize the crowding-out effect by dampening monetary and administrative incentives through nondistribution constraint and self-governance orientation, respectively. This facilitates not only economic survival of nonprofit firms but also maximization of utility of their intrinsically motivated stakeholders. [PUBLICATION ABSTRACT]